Proficiency examination in English language: Needs analysis and methodological proposals - Luz Saes, Maria Elizete (The ESPecialist, 2014)
The purpose of this work is to provide tools for reflections on some learning difficulties presented by students when they are submitted to English proficiency examinations, as well as to suggest some methodological proposals that can be implemented among didactic support groups, monitoring or in classrooms, by means of face-to-face or distance learning activities. The observations resulting from the performance presented by the students have motivated the preparation of this paper, whose theoretical assumptions are based on the needs analysis of the target audience, the exploration of oral and written discursive genres and the possibilities of interaction provided by technological mediation.